The effectiveness of problem-based thematic learning module to improve primary school student’s critical thinking skills - Twiningsih, Anik; Sajidan, Sajidan; Riyadi, Riyadi (Jurnal Pendidikan Biologi Indonesia, 2019)
Thematic learning is considered as efficient as the students taught learn in coherent context and holistic way, as well as associate the concepts they learnt with their surrounding and real-life examples. The aim of the study was to identify the effectiveness of the problem-based thematic learning module prototype to improve students' critical thinking skills. This research and development were conducted based on Borg and Gall model. The module effectiveness was tested using pre-experimental design. The sampling technique used was cluster random sample which employed as many as 33 students in which the data collection technique used was test. The data gained was analyzed using paired sample t-test. The results showed that the students’ post-test score of critical thinking skills were significantly differed from their pre-test score. Therefore, the developed module can improve student critical thinking skills effectively. Moreover, it is suggested that teacher should apply a mixed method of teaching as it helps to strengthen students’ critical thinking skills.